Investigação dos mecanismos neurobiológicos envolvidos nas propriedades reforçadoras, sensibilização locomotora e reinstalação da autoadministração de etanol - Bianchi, Paula Cristina (2018)
Alcohol is the most consumed drug in Brazil and in many other countries in the world. The high rate of relapse in alcohol-dependent individuals remains a central challenge for treating alcoholism. Several studies in human and animal models of addiction show that environmental stimuli associated with previous drug use can provoke relapse to drug use. However, the neurobiological mechanisms involved in the alcohol relapse induced by environmental stimuli are not fully understood. Recent studies have been demonstrated that the synaptogenic effect of matricellular protein Hevin can promote striatal neuroplasticity that can modulate motivational properties of drugs. Despite that, the role of Hevin in alcohol addiction related behaviors has not been investigated. In the present study, we investigated the participation of pre-limbic cortex (PL); orbitofrontal cortex (OFC), and nucleus accumbens (NAc) in the context-induced reinstatement of alcohol-seeking in rats. We also evaluated the effect of Hevin inhibition in astrocytes or parvalbumin interneurons (PV) in the striatum on ethanol consumption, ethanol-induced conditioned place preference (CPP) and locomotor sensitization in mice. Our results demonstrated that: a) there were no differences between male and female rats in the reinstatement of alcohol-seeking behavior; b) re-exposure to the drug-context reinstated alcohol-seeking and increased Fos expression in the OFC, PL and NAc core and shell; c) reversible inactivation of the OFC or NAc core attenuated context-induced reinstatement of alcohol-seeking; d) there was more activation of the PL – NAc core pathway in the animals exposed to the drug-context, compared to those that were exposed to the extinction-context; e) inhibition of astrocytic Hevin into NAc did not alter ethanol consumption, but decreased alcohol-induced CPP; f) inhibition of astrocytic and neuronal Hevin in the dorsal striatum decreased locomotor sensitization induced by alcohol; and g) repeated alcohol injections in mice increased the volume of dendritic compartments of PV interneurons in the dorsal striatum.